Non thermal plasma in liquid media: Effect on inulin depolymerization and functionalization. (1st March 2020) - Nastase, Raluca; Fourré, Elodie; Fanuel, Mathieu; Falourd, Xavier; Capron, Isabelle
Highlights: A novel double dielectric barrier discharge plasma reactor with a liquid interface has been designed. It is possible to totally convert inulin into 100 % fructose and glucose. No degradation products are generated. Combined analytical results evidenced the acidic attack of the glycosidic bond leading to depolymerization. Abstract: We report the complete conversion of inulin in gas/liquid media by a dielectric barrier discharge plasma at atmospheric pressure. Depending on the plasma treatment time (from 1 to 30 min) and the chemical nature of the gases (air, oxygen, nitrogen), it was possible to depolymerize inulin into fructo-oligosaccharides with a degree of polymerization under 5 or to achieve a total conversion of inulin into its two monomeric constituents, fructose and glucose in 20 min, without any degradation products. Combined results from liquid chromatography (HPLC), solid state Nuclear Magnetic Resonance (ssNMR) and mass spectroscopy revealed that the breakage of the β 1-4-bridged oxygen occurs by an acidic attack, following the oxidation of the polymer. Infrared spectroscopy revealed the oxidation and breakage of the polymer and also adsorption of nitrate species. Non thermal plasma treatment appears as a promising technology for the efficient production of mono and oligosaccharides from various sources for the added value molecules in food and pharmaceutical application domains.